Severe SARS-CoV-2 Infection Inhibits Fibrinolysis Leading to Changes in Viscoelastic Properties of Blood Clot: A Descriptive Study of Fibrinolysis in COVID-19 - Hammer, Stefanie; Häberle, Helene; Schlensak, Christian; Bitzer, Michael; Malek, Nisar P.; Handgretinger, Rupert; Lang, Peter; Hörber, Sebastian; Peter, Andreas; Martus, Peter; Mirakaj, Valbona; Gawaz, Meinrad; et al. (Thrombosis and haemostasis, 2021)
Abstract Background Accumulating evidence indicates toward an association between severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection and procoagulatory state in blood. Thromboelastographic investigations are useful point-of-care devices to assess coagulation and fibrinolysis. Objectives We investigated the hypothesis that the procoagulatory state in COVID-19 patients is associated with impaired fibrinolysis system. Methods Altogether, 29 COVID-19 patients admitted to normal wards or to the intensive care unit (ICU) were included in this descriptive study. Whole blood samples were investigated by thromboelastography to assess coagulation and fibrinolysis. Additionally, standard routine coagulation testing and immunoassays for factors of fibrinolysis as plasminogen activator inhibitor-1 (PAI-1), tissue plasminogen activator (tPA), plasminogen activity and α2-antiplasmin (A2AP) were performed. Results A significantly increased lysis resistance and a significantly longer time of lysis after adding tissue plasminogen activator were observed in blood samples from ICU COVID-19 patients compared with healthy controls (maximal lysis: 3.25 ± 0.56 vs. 6.20 ± 0.89%, p = 0.0127; lysis time: 365.7 ± 44.6 vs. 193.2 ± 16.3 seconds, p = 0.0014). PAI-1 activity was significantly higher in plasma samples of ICU COVID-19 patients (PAI-1: 4.92 ± 0.91 vs. 1.28 ± 0.33 U/mL, p = 0.001). A positive correlation between the activity of PAI-1 and lysis time of the formed clot ( r = 0.70, p = 0.0006) was observed. Conclusion Our data suggest that severe SARS-CoV-2 infection is associated with impaired fibrinolytic activity in blood, where fibrinolytic inhibitors are elevated leading to an increased resistance to clot lysis. Thromboelastography could offer a tool to investigate the contribution of the fibrinolytic status to the procoagulatory condition in COVID-19.